2016
DOI: 10.3892/mmr.2016.6062
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular weight fucoidan inhibits the differentiation of osteoclasts and reduces osteoporosis in ovariectomized rats

Abstract: Abstract. Fucoidan is a type of sulfated polysaccharide isolated from seaweed. The present study used ovariectomized Sprague-Dawley rats, which were treated with fucoidan. The effects of fucoidan on bone metabolism, density and microarchitecture were assessed using micro-computed tomography (CT), histomorphometric analysis, biochemical markers of bone metabolism (Serum procollagen type I N propeptide and C-terminal telopeptide-1) and tests of mechanical competence of the femur. In addition, the effects of low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
(44 reference statements)
2
17
0
Order By: Relevance
“…Our results are further supported by Jin et al 40 and Lu et al 17 LMW FUC prevented bone turnover in ovariectomized rats, as micro‐CT showed a higher BV/TV and TbTh in rats treated with FUC than without FUC 40 . Histomorphometric analysis further demonstrated this, with a reduced bone turnover rate was found in the FUC group compared to ovariectomized rats without FUC 40 . Lu et al also demonstrated reduced bone turnover: micro‐CT and bone histomorphometry found that FUC treatment markedly prevented lipopolysaccharide‐induced bone erosion in mice 17 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are further supported by Jin et al 40 and Lu et al 17 LMW FUC prevented bone turnover in ovariectomized rats, as micro‐CT showed a higher BV/TV and TbTh in rats treated with FUC than without FUC 40 . Histomorphometric analysis further demonstrated this, with a reduced bone turnover rate was found in the FUC group compared to ovariectomized rats without FUC 40 . Lu et al also demonstrated reduced bone turnover: micro‐CT and bone histomorphometry found that FUC treatment markedly prevented lipopolysaccharide‐induced bone erosion in mice 17 .…”
Section: Discussionsupporting
confidence: 92%
“…According to literature, fucoidan can affect bone health by influencing osteoblast differentiation as well as bone resorption [ 36 , 37 ], both processes that depend on VEGF as a central regulatory molecule. In contrast to our observation, a number of studies show that fucoidans promote osteoblast differentiation [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its osteogenic effects, 3D culture systems are predicted to narrow the gap between in vitro studies and clinical trials [150]. Of the in vivo experiments performed, LMWF has been shown to inhibit osteoclast differentiation and bone resorption in ovariectomized Sprague-Dawley rats, demonstrating its potential in the treatment of osteoporosis [151]. The extraction of LMWF from fresh Sargassum hemiphyllum also increased bone density and ash weight in C57BL/6J female mice [152].…”
Section: Non-classical Activitiesmentioning
confidence: 99%